Currency, Art, and Economic Crisis. (3rd April 2018) - Shtromberg, Elena
Abstract : The condition of a country's currency is perhaps one of the most effective barometers of its economic state, a topic that has been amply examined by economists. Currency as artistic medium is lesser-explored terrain and yet its study can prove revealing of a country's economic and historical circumstances while poignantly commenting on the whimsical nature of the art market and the commercial value of works of art. For this study, I will explore the work of artists who employed currency as commentary on their country's respective economic crises and the political conditions that led to them. I have selected a small sample of artworks with currency focusing specifically on the circulation of the US dollar, or rather it symbolic dominance, in Latin Ameircan economies. In this study, I examine three case studies spanning several decades, among them: a series of banknotes by Brazilian artist Cildo Meireles entitled Zero Dollar, created during the late 1970s and 1980s; a multimedia installation Circulante (Circulating) from 1998 by Ecuadorian artist Patricio Palomeque, and the video piece Inversión from 2011 by Cuban artist Glenda León. All three artists used their work to foreground the instability and fragile structures underpinning currency while critiquing the expansion and reach of the US dollar in their countries.